The Consensus Project and Three Levels of Deliberation - Ani, I.E. (Dialogue-Canadian Philosophical Review, 2018)
The basic argument is that the consensus debate has not been very meaningful until now because consensus has not been closely studied as a concept, and deliberation has not been studied precisely in terms of the propensity to reach common agreement. In particular, deliberation—as well as issues for deliberation—has not been categorized into different levels with a view to exposing the varying challenges of reaching common agreement and the kinds of deliberative approaches entailed in each category. In this research, I attempt to provide this categorization in order to clarify the debate. Copyright © Canadian Philosophical Association 2018
Keywords: Consensus; Deliberation; Facts; Interests; Reasons; Values